Design of a photovoltaic solar irrigation system for the evaluation of phenology in jalapeño pepper - Rodríguez-Chiunti, Miguel Ángel; Vidal-Gamboa, Adán (Renewable Energy, Biomass & Sustainability, 2021)
The need for higher crop productivity per unit area due to the growing population of the world is an extreme need, one of the possible approaches to cover this type of needs is photovoltaic solar irrigation systems. Considering the availability of solar radiation and the lack of electrical energy in the experimental study area, the design of a solar photovoltaic drip irrigation system is justified in an experimental area of ​​60 m² under shade mesh in Cosamaloapan, Veracruz, where the estimation of the solar radiation was carried out with the model provided according to the geographical location by means of the FAO CROPWAT software. For the calculation of evapotranspiration, the Penman-Monteith method was used, the data of the cultivation coefficient (Kc) were taken from the guide for the determination of the water requirements of the FAO crops and later these data were annexed to the aforementioned software for subsequent processing in the calculation of the water requirement of the crop. The main objective of this work was to design a photovoltaic solar irrigation system for the evaluation of phenology in the jalapeño pepper (Capsicum annuum, L.) under shade mesh. The analysis of the results indicates that during the months that included the development of the research, a daily average of 10.5 MJ/m² (2.91 Kwh/m²) was presented, which allowed charging the 9 A and 12 V battery in a time of 4 hours at 80 % charging efficiency through the 50 W solar panel used. The 70 W irrigation pump used was operated daily in a time of 16 minutes to cover the water demand of each plant (260 ml).